VD_FINDINFO HC / 2011 / 225 vom 4. April 2011 - VD Tribunal cantonal (2011)
MESURE PROVISIONNELLE, NOUVEAU MOYEN DE PREUVE, NOUVEAU MOYEN DE FAIT | 176 al. 3 CC, 276 al. 1 CC, 308 al. 1 let. b CPC (CH), 317 al. 1 CPC (CH)